A Bibliometric Analysis of Policy-Driven Religious Moderation Education Research in Indonesia: Trends, Evolution, and Research Landscape - Ahmad Saibudin; Lismawati (Jurnal Paedagogy, 2026)
This study systematically maps the intellectual landscape of religious moderation education in Indonesia by analyzing publication growth, identifying key influential actors, and tracing thematic evolution in order to provide a strategic theoretical framework for inclusive Islamic education policy. A bibliometric approach was employed, analyzing metadata from 149 Scopus-indexed articles published between 2015 and 2025. The results indicate that the discourse has reached a stage of “policy-driven maturity,” characterized by an exponential increase in publications after 2020, largely in response to national policy mandates. Thematic analysis reveals a core dualism between the “Education Implementation” and “Policy Response” clusters, illustrating how government directives are translated into pedagogical strategies. However, the findings also highlight a pronounced “silo effect” in institutional collaboration, primarily driven by localized and competitively allocated research funding schemes (e.g., BOPTN and Litapdimas), which limit cross-institutional synergy. This study concludes that research on religious moderation in Indonesia is systematically shaped by government policy and contributes significantly to the achievement of SDG 4 (Quality Education). Nevertheless, stronger cross-institutional collaboration is essential to sustain and further develop inclusive educational frameworks.